Workforce agility: a systematic literature review and research agenda - Alviani, Devi; Hilmiana; Widianto, Sunu; Muizu, Wa Ode Zusnita (Frontiers in Psychology, 2024)
Research on workforce agility is still in its early stages. It relies on diverse theories and exhibits limitations in theorization, yet it has demonstrated numerous beneficial impacts. In this review, we provide a multilevel model of workforce agility (i.e., individual and organization). The model contains a summary of variables studied as a nomological network concerning workforce agility (e.g., predictors, mediators, moderators, and outcomes) and an overview of various theories (e.g., dynamic capability theory, social exchange theory, resource-based theory) supporting each relationship and explaining the underlying mechanisms. In this context, we propose future research to empirically test the multilevel model of workforce agility and examine the predictive value of employee and organization variables. Furthermore, we evaluate recommendations made by previous researchers regarding the development of the workforce agility concept. From this synthesis, we successfully identify nine relevant research directions to explore further the concept and practice of workforce agility in the future. 2022). Second, the current research reaffirms a deeper understanding of the mediating mechanisms, moderating, and influencing factors of workforce agility, as well as the supporting theoretical